2002
DOI: 10.1002/jcb.10137
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization and DNA interaction of protein disulfide isomerase ERp57 in mammalian cells

Abstract: Protein disulfide isomerase ERp57 is localized predominantly in the endoplasmic reticulum, but is also present in the cytosol and, according to preliminary evidence, in the nucleus of avian cells. Conclusive evidence of its nuclear localization and of its interaction with DNA in vivo in mammalian cells is provided here on the basis of DNA-protein cross-linking experiments performed with two different cross-linking agents on viable HeLa and 3T3 cells. Nuclear ERp57 could also be detected by immunofluorescence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 30 publications
(26 reference statements)
0
62
1
Order By: Relevance
“…However, the presence of ERp57 in the nucleus has now been firmly established by a number of observations, carried out in different laboratories and with a variety of experimental techniques. Treatments of various intact mammalian cultured cells with DNA-protein crosslinking agents (formaldehyde, cis-platinum and UV irradiation have been used) have demonstrated that ERp57 and DNA are indeed bound in vivo, in experimental conditions respecting the integrity of cellular structures [59,68]. Immunofluorescence studies performed in a few cases where exceptionally the ERp57 nuclear content was very high confirmed the cross-linking results [52].…”
Section: Erp57 In the Nucleusmentioning
confidence: 71%
“…However, the presence of ERp57 in the nucleus has now been firmly established by a number of observations, carried out in different laboratories and with a variety of experimental techniques. Treatments of various intact mammalian cultured cells with DNA-protein crosslinking agents (formaldehyde, cis-platinum and UV irradiation have been used) have demonstrated that ERp57 and DNA are indeed bound in vivo, in experimental conditions respecting the integrity of cellular structures [59,68]. Immunofluorescence studies performed in a few cases where exceptionally the ERp57 nuclear content was very high confirmed the cross-linking results [52].…”
Section: Erp57 In the Nucleusmentioning
confidence: 71%
“…Knockout mice of ERdj5, Prdx4, and Ero1a/b (see later section) showed less severe phenotypes, which suggests that their roles can be compensated for by other factors (Iuchi et al 2009;Hosoda et al 2010;Zito et al 2010a). In addition, some ER proteins appear to possess functions outside the ER, such as in mitochondria or nucleus (P5 and ERp57) (Coppari et al 2002;Kimura et al 2008). Clarifying their detailed roles and regulatory mechanisms will be an exciting topic for future work (AppenzellerHerzog and Ellgaard 2008).…”
Section: Disulfide Bond Formationmentioning
confidence: 99%
“…We have suggested that ERp57, through its disulphide isomerase activity, might have a role in the proper folding and compartmentalization of TUBB3 in response to paclitaxel treatment. Though mainly localised in the ER, ERp57 has been detected in the cytosol, where it participates to signal transduction and transcription regulation by activation of STAT3 (11) and in association with the cytoskeleton (3), and in the nucleus, where it influences the DNA binding of transcription factors or of structural nuclear proteins (49,50) and is involved in the cellular response to drug treatment (3,13,51).…”
Section: Discussionmentioning
confidence: 99%